Prevalence and Risk Factors for Needle Stick Injuries among Health Workers at Hospitals: A Literature Review - Balgahoom1, Najwa Tasha Nagieb; Hanifah, Naura; Pou, Rudy; Chudri, Juni (Universitas Muhammadiyah Semarang, 2024)
Background: Needle Stick Injury (NSI) is the main cause of infections in health workers that are transmitted through blood, such as human immunodeficiency virus (HIV), hepatitis B and hepatitis C. The incidence of NSI exposure in the workplace in developing countries is estimated to be much higher and most cases are not even reported. by 75%. The purpose of writing this literature review is to determine the prevalence of NSI among health workers and identify risk factors for NSI so that there is increased awareness of NSI among health workers. Method: search for articles in Google Scholar, PubMed and Crossref databases using the keywords: risk factors + needle stick injury + health workers + hospital. The inclusion criteria for research subjects are healthcare workers, articles published in 2018-2023, accessible (open access), saved in portable document format (PDF) which can be downloaded for free, and in English. Results: The prevalence of NSI in each country is different, due to the many risk factors that cause NSI.. Conclusion: by understanding the risk factors for NSI, prevention efforts can be made. Hospital management can evaluate and improve existing programs and standard operating procedures, evaluate working hours and conduct training programs related to occupational health and safety.